The Legacy of the Soviet Agricultural Research System for the Republics of Central Asia and the Caucasus - Morgounov, A.; Zuidema, Larry (International Service for National Agricultural Research, 2001)
The primary legacy of the Soviet agricultural research system for the former Soviet republics of Central Asia and the Caucasus was a highly organized, fully funded, and overcapitalized agricultural research establishment. The new republics inherited a large number of research institutions and a huge complement of scientific staff. Evolution of their economies and their agriculture, however, challenges these countries to reform their technology system to make it responsive and effective. Up to now, a preservationist strategy has been the dominant means for dealing with agricultural research structure, implying the maintenance of existing institutes as a system. This is true despite a strong desire by scientists and government to optimize agricultural research. Future development in these countries depends largely on the political will of agricultural research system leaders to take bold steps to reform agricultural research according to a sound strategy that takes into account changing demand for agricultural research as reflected in emerging local and international markets.